Defining “Normal” basal serum tryptase levels: a context-dependent approach to improve diagnostics in systemic mastocytosis - Crupi, Francesca; Caroprese, Jessica; Mannelli, Francesco (Frontiers in Allergy, 2025)
Serum tryptase level has long been used as a biomarker in clinical practice to suspect mast-cell associated disorders. Basal serum tryptase (BST) above 20 ng/ml represents a minor criterion according to WHO and ICC for the diagnosis of systemic mastocytosis (SM) although normal BST value does not exclude the diagnosis. Nevertheless, BST can be elevated also due to non-SM related diseases as well as hereditary alpha-tryptasemia (HαT), an autosomal dominant germline condition that consists in the increase of the number of copies of the TPSAB1 gene encoding the alpha isoform of tryptase. The prevalence of HαT is estimated at around 5% of the general population. Individuals with HαT genotype can be asymptomatic; however, some of them can experience a range of symptoms with a large variability in type and severity, posing a problem of differential diagnosis with SM. The increasing awareness on a potentially SM underlying diverse clinical manifestations has led to excessive BST testing by several specialists, a trend that risks over interpreting some borderline results. The interpretation of elevated BST should thus be carefully appraised in specific clinical contexts on individual basis. This review is intended to examine the existing literature on this topic and offers a guide for interpreting the BST to rationalize the application of invasive diagnostic procedures.